ลำดับคำของศัพท์การประกอบอาหารในชื่ออาหารไทย ลาว เขมร และจีน Word order of the Cooking Terms in Thai, Lao, Khmer and Chinese Cuisine - ตรงดี ธนานันท์; แซ่อึ๋ง วราลักษณ์; แซ่ว่อง อุไรวรรณ; Aixia, Cui; Shangyue, Huang (Chophayom Journal, 2017)
บทคัดย่อ อาหารไทยบางชนิดมีได้สองชื่อ เช่น ผัดเผ็ดปลาดุก และ ปลาดุกผัดเผ็ด ศัพท์การประกอบอาหาร ผัด ปรากฏได้ทั้งหน้าและหลังคำนามว่า ปลาดุก ความขัดแย้งนี้เป็นที่มาของการศึกษาว่า ในภาษาอื่น เช่น ภาษาลาว ภาษาเขมร และ ภาษาจีนมีปรากฏการณ์เช่นนี้หรือไม่ ข้อมูลส่วนใหญ่ได้จากการสัมภาษณ์เจ้าของภาษา ผลการศึกษาพบว่า ศัพท์การประกอบอาหารบางคำในภาษาไทยปรากฏได้ทั้งหน้าและหลังคำนามซึ่งเป็นวัตถุดิบของอาหารศัพท์การประกอบอาหารส่วนใหญ่ในภาษาลาวปรากฏหน้าวัตถุดิบ ศัพท์การประกอบอาหารในภาษาเขมรทุกคำปรากฏหลังวัตถุดิบ และศัพท์การประกอบอาหารในภาษาจีน ทุกคำปรากฏหน้าวัตถุดิบ การวางกริยาหน้าคำนามในภาษาไทยและภาษาลาวเพื่อสร้างคำประสมนั้น ถือว่าขัดหลักไวยากรณ์ ดังนั้นจึงต้องหาคำอธิบาย คำตอบก็คือ ศัพท์การประกอบอาหารเหล่านั้นได้ผ่านกระบวนการแปลงชนิดคำจากคำกริยาให้เป็นคำนาม ซึ่งเป็นกระบวนการสร้างคำประเภทหนึ่งในภาษาไทยและภาษาลาว คำสำคัญ : ศัพท์การประกอบอาหาร การแปลงชนิดคำ ภาษาไทย ภาษาลาว ภาษาเขมร ภาษาจีน ABSTRACT In some Thai cuisine, it is apparent that there are 2 words for the same dish as ‘pla:duk phat phet’ (catfish-fry-spicy) and ‘phat phet pla: duk’ (fry-spicy-catfish). The cooking term, to fry, can be placed both before and after the noun ‘catfish’. This discrepancy is the rational of this article to find out whether in other languages like Lao, Khmer, and Chinese the cooking terms can be placed before or after the raw materials. Most of the data is obtained by means of interviewing native speakers. It is found that in Thai cuisine, some cooking terns are placed before the raw materials, in Lao before the raw materials, in Khmer after the raw materials, and in Chinese before the materials. Explantions are required since, in Thai and Lao, it is ungrammatical to place a verb before a noun to form a compound noun. The answer is that in Thai and Lao cuisines, some verbs of cooking are derived to be nouns via the process of conversion or zero derivation. This process is a kind of word formations in Thai and Lao.